ARID1A-dependent permissive chromatin accessibility licenses estrogen-receptor signaling to regulate circadian rhythms genes in endometrial cancer. (1st November 2020) - Hu, Hanyang; Chen, Zhiguo; Ji, Lulu; Wang, Yanling; Yang, Mengzhen; Lai, Rujie; Zhong, Yu; Zhang, Xiaoli; Wang, Lin
Abstract: Estrogen receptor α (ER) acts as an oncogenic signal in endometrial endometrioid carcinoma. ER binding activity largely depends on chromatin remodeling and recruitment of transcription factors to estrogen response elements. A deeper understanding of these regulatory mechanisms may uncover therapeutic targets for ER-dependent endometrial cancers. We show that estrogen induces accessible chromatin and ER binding at a subset of enhancers, which form higher-order super enhancers that are vital for ER signaling. ER positively correlates with active enhancers in primary tumors, and tumors were effectively classified into molecular subtypes with chromatin accessibility dynamics and ER-dependent gene signature. ARID1A binds within ER-bound enhancers and regulates ER-dependent transcription. Knockdown of ARID1A or fulvestrant treatment profoundly affects the gene-expression program, and inhibits cell growth phenotype by affecting the chromatin environment. Importantly, we found dysregulated expression of circadian rhythms genes by estrogen in cancer cells and in primary tumors. Knockdown of ARID1A reduces the chromatin accessibility and ER binding at enhancers of the circadian gene ARNTL and BHLHE41, leading to a decreased expression of these genes. Altogether, we uncover a critical role for ARID1A in ER signaling and therapeutic target in ER-positive endometrial cancer. Highlights: Estrogen induces accessible chromatin and ER binding at a subset of enhancers in endometrial cancer cells. ARID1A binds within ER-bound enhancers and regulates ER-dependent transcription. Silencing of ARID1A inhibits cell growth and invasion. ARID1A and ER corporately activate the aberrant circadian rhythms gene transcription.